STUDI SAMBUNGAN KOMPOSIT BAJA RINGAN-LAMINASI KAYU DENGAN ALAT SAMBUNG BAUT - , ANINDHA DYAH D ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Cold formed steel, which is nowadays popular in Indonesia for roof structures, has small thickness that makes it easy to buckling. Combining cold formed steel with timber would be an effective solution for buckling problem prevention. There were some previous studies about composite of cold formed steel and timber, however topic about the connection is very limited. This study is aimed to find suitable connections system for composite cold formed steel-timber lamina. Cold formed steel 75Z08 and Swietenia mahagoni were used in this study. Two bolts of 8 mm in diameter were used in composite connection samples. There were twelve joint specimens: six joints loaded in parallel loading direction and another six joints loaded in perpendicular loading direction. In both parallel and perpendicular loaded joints, two different side members were used: steel plate (t = 4 mm) and plywood (SG = 0.41